NUMERICAL AND EXPERIMENTAL INVESTIGATION OF FLOW FIELD INSIDE ARTERIES AND VEINS (Journal of Engineering, 2024)
Numerical and experimental investigation of blood flow through stenotic and tapered arteries under pulsation condition are studied. Blood is considered as non-Newtonian fluid. Artery is considered as a rigid wall tapered vessel with different tapering angles (0.5o, 1o ,1.5o ), as well as, straight vessel for comparison. The governing equations have been written in stream- vorticity method and are transformed into generalized coordinate system. The time marching has been employed to solve the resulting partial differential equations. The experimental work carried out to examine pressure in vessel and pressure drop across the stenosis under pulsation condition. Differential pressure transducer coupled to the data acquision card type PCI-911DG, which is built in computer was used to record pressure data. The results showed that, as a tapering angle increases (0.5o , 1o , 1.5o ) both wall shear stress and pressure drop increasing, also as stenosis increases (50%, 60%, 75%) both wall shear stress and pressure drop increasing. These behaviors are found in literature, pressure drop is used to compare experimental data and numerical results, which indicates agreement. As the distance into taper section increased both wall shear stress and pressure drop are increased, as well as, both wall shear stresses and pressure drop increased with inlet flow rate increased, while decreased with inlet diameter increase.